2014
DOI: 10.2108/zs140060
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Transcription Regulatory Mechanism of Otx During the Development of the Sensory Vesicle in Ciona intestinalis

Abstract: Establishment of the anterior-posterior axis is an important event in the development of bilateral animals. A homeodomain transcription factor, Otx, is important for the formation of the anterior part of the embryo, and its mRNA is expressed in a continuous manner in a wide range of animals. This pattern of expression is thought to be important for the formation of anterior neural structures, but the mechanism that regulates Otx expression remains largely unknown. Towards understanding how the transcription of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Otx is continuously expressed in the DA-lineage cells from cleavage to at least the tailbud stages, and the transcription regulatory mechanisms of Otx change several times during the development (Hudson and Lemaire, 2001;Oonuma et al, 2014). It has been suggested that from the cleavage to the early gastrula stages, Otx expression is regulated by the transcription factors GATA and Ets activated by FGF signaling (Bertrand et al, 2003), whereas the transcription factors Sox, Zic and Fox have been suggested to regulate the transcription of Otx from the mid to late gastrula stages (Oonuma et al, 2014). Either of these two pathways, i.e.…”
Section: The Role Of Otx In Da Cell Development In Cionamentioning
confidence: 99%
“…Otx is continuously expressed in the DA-lineage cells from cleavage to at least the tailbud stages, and the transcription regulatory mechanisms of Otx change several times during the development (Hudson and Lemaire, 2001;Oonuma et al, 2014). It has been suggested that from the cleavage to the early gastrula stages, Otx expression is regulated by the transcription factors GATA and Ets activated by FGF signaling (Bertrand et al, 2003), whereas the transcription factors Sox, Zic and Fox have been suggested to regulate the transcription of Otx from the mid to late gastrula stages (Oonuma et al, 2014). Either of these two pathways, i.e.…”
Section: The Role Of Otx In Da Cell Development In Cionamentioning
confidence: 99%